Pengaruh Kinerja Nanopartikel TiO2, ZnO dan GO pada Membran PSf Neat untuk Pengolahan Limbah Batik - Nugraheni, Ratih Estu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Membrane technology is currently experiencing rapid growth. Various applications of membranes have been implemented in everyday life, one of which is wastewater treatment. In Indonesia, batik is recognized as a UNESCO heritage art form. However, batik wastewater has not been properly treated, leading to environmental damage. This research aims to investigate the effects of TiO2, ZnO, and GO nanoparticles on neat PSf membranes. These three nanoparticles were chosen for their ability to modify the hydrophilicity and porosity of the membrane. The results indicated that TiO2, ZnO, and GO nanoparticles influenced the separation capability for COD, ammonia, Cr, and color content in the modified membranes. The enhanced separation ability of the modified membranes suggests that TiO2, ZnO, and GO nanoparticles have the potential to reduce environmental damage.